The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3892/ijo.2017.4183
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg3 targets cancer stem cells and tumor angiogenesis to inhibit colorectal cancer progression in vivo

Abstract: Anti-angiogenic therapy has been successfully applied to treat colorectal cancer (CRC). Ginsenoside Rg3, derived from the Chinese herb ginseng, has anti-vascularization effects and can inhibit tumor growth and metastasis, and can sensitize cancer cells to chemotherapy. Therefore, in the present study, we investigated whether Rg3 could be appropriate for CRC treatment. Growth of CRC cells was assessed by an MTT (methyl thiazolyl tetrazolium) assay in vitro and using orthotopic xenograft models in vivo. mRNA exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 46 publications
7
62
0
Order By: Relevance
“…It induces cell cycle arrest at G1 phase in human melanoma A375, and multiple myeloma U266, RPMI 8226 and SKO-007 cells [239,240], and inhibits cell migration in human colorectal cancer LoVo, SW-620 and HCT-116 cells [240]. Ginsenoside Rg3 can also modulate the tumor environment through inhibiting angiogenesis and enhancing anti-tumor immune responses [241]. Moreover, ginsenoside Rh2 exhibits anti-tumor activity in human NSCLC H1299 cells and H1299 xenograft mice, through the induction of ROS-mediated ER-stress-dependent apoptosis [242].…”
Section: Ginsenosidesmentioning
confidence: 99%
See 1 more Smart Citation
“…It induces cell cycle arrest at G1 phase in human melanoma A375, and multiple myeloma U266, RPMI 8226 and SKO-007 cells [239,240], and inhibits cell migration in human colorectal cancer LoVo, SW-620 and HCT-116 cells [240]. Ginsenoside Rg3 can also modulate the tumor environment through inhibiting angiogenesis and enhancing anti-tumor immune responses [241]. Moreover, ginsenoside Rh2 exhibits anti-tumor activity in human NSCLC H1299 cells and H1299 xenograft mice, through the induction of ROS-mediated ER-stress-dependent apoptosis [242].…”
Section: Ginsenosidesmentioning
confidence: 99%
“…For the promotion of immunity, ginsenoside Rg3 can enhance lymphocyte proliferation and T helper type 1 cell (Th1)-related cytokine secretion including IL-2 and IFN-γ in hepatacellular carcinoma H22-bearing mice, and inhibit tumor growth partly through the induction this cellular immunity [259]. Ginsenoside Rg3 can also down-regulate the levels of B7-H1 and B7 homolog 3 (B7-H3), immunoglobulin-like immune suppressive molecules, to modulate tumor microenvironment and enhance anti-tumor immunity, and these molecules are negatively associated with overall survival in colorectal cancer patients [241]. It also ameliorates cisplatin resistance by down-regulating B7-H1 levels and resuming T cell cytotoxicity in human NSCLC A549 and A549/DDP cells [260].…”
Section: Ginsenosidesmentioning
confidence: 99%
“…Ginsenoside Rg3, the main component of Ginsenoside, has been shown to inhibit tumor progression and chemoresistance, for example, Ginsenoside Rg3 attenuates temozolomide resistance and epithelial‐mesenchymal transition (EMT) progression in glioblastoma; Ginsenoside Rg3 inhibits prostate cancer cell proliferation through inducing cell cycle arrest . Recent studies showed that Ginsenoside Rg3 could target CSCs in colorectal cancer and Ginsenoside Rg3 could enhance cisplatin sensitivity via blocking EMT process and stemness in lung cancer cells . However, it is unclear whether Ginsenoside Rg3 could target CSCs and reverse osimertinib resistance in NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Many randomized, prospective clinical trials indicate that ginsenoside Rg3 can effectively treat digestive system cancer and improve its side effects. For example, Tang et al [33,34] reported that ginsenoside Rg3 can target cancer stem cells and tumor angiogenesis to inhibit CRC progression by downregulating C/EBPβ/NF-κB signaling. Aziz et al [35] found that ginsenoside Rg3 induces FUT4-mediated apoptosis in H. pylori CagA-treated GC cells by regulating SP1 and HSF1 expressions.…”
Section: Summary Of Previous Evidencementioning
confidence: 99%